2011
DOI: 10.1016/j.japwor.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The adoption of poison pills and managerial entrenchment: Evidence from Japan

Abstract: The purpose of this paper is to examine the effect of poison pills on shareholder wealth using cases of Japanese firms that announced the adoption of poison pills between April 2005 and May 2006. We find that announcements of poison pill defenses reduce shareholder wealth by a significant amount. We also investigate the relationship between this negative stock price response to poison pills and a manager's incentive for entrenchment, using conditional event study methods. We confirm that the probability of ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…On the one hand, the hypothesis of the alignment of shareholder interests envisions that the adoption of poison pills may be influenced by factors which seek to reduce agency conflicts between managers and shareholders (Heron & Lie, 2006;Heron & Lie, 2015), such as mechanisms related to corporate governance. On the other hand, it is also possible that its adoption is not influenced by aspects that seek to benefit shareholders (notably minority shareholders), but rather to maintain the current managers in their positions, as demonstrated by the managerial entrenchment hypothesis (Arikawa & Mitsusada, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the hypothesis of the alignment of shareholder interests envisions that the adoption of poison pills may be influenced by factors which seek to reduce agency conflicts between managers and shareholders (Heron & Lie, 2006;Heron & Lie, 2015), such as mechanisms related to corporate governance. On the other hand, it is also possible that its adoption is not influenced by aspects that seek to benefit shareholders (notably minority shareholders), but rather to maintain the current managers in their positions, as demonstrated by the managerial entrenchment hypothesis (Arikawa & Mitsusada, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Arikawa and Mitsusada (2011) showed that adoption of poison pills reveals the manager's preference for entrenchment. In particular, they found that a CEO with longer tenure was more likely to adopt a poison pill when the performance of the firm was poor.…”
mentioning
confidence: 99%
“…27 See, for example, Bebchuk and Cohen (2005), Gompers, Ishii, and Metrick (2003), and Hermalin and Weisbach (2003). Arikawa and Mitsusada (2008) show that Japanese firms experience negative abnormal returns right after announcing introductions of new poison pills. 26 Such stable shareholding prevented hostile takeovers of listed firms in Japan since the early 1950s.…”
Section: Business Practices and Policy Implicationsmentioning
confidence: 99%